DIPG-05. How do potassium channels contribute to the growth and invasion of highly-aggressive brain cancers?. (3rd June 2022) - Boyle, Yasmin; Fletcher, Emily; Johns, Terrance
Abstract: Glioblastoma (GBM) is a lethal form of high-grade glioma with a dismal median survival time of just 15 months. Characterised by its' highly diffuse and intrinsic growth pattern, GBM invades the healthy brain at an alarming rate. While diffuse midline glioma (DMG) is a much rarer disease, it is even more lethal, with a 5-year survival rate of just 2%. Though GBM is largely diagnosed in adults, DMG primarily affects young children aged 5-9 years and accounts for 10% of all childhood CNS cancers. Thus, while rare, DMG is highly aggressive and currently has no effective treatments to extend survival times beyond the median of 9 months. There is a pressing need for the development of novel and improved targeted therapies for each of these devastating diseases. Ion channels have long been implicated in the progression of numerous cancer types, due to their integral roles in proliferation, cell cycle transition, apoptosis, migration, and cellular plasticity. Voltage-gated potassium channels (VGKCs), in particular, have strong links to the key processes of proliferation, migration and invasion in GBM tumours. Given that the majority of GBM-related deaths are attributed to secondary tumours and metastasis, targeting proteins that are integral to these processes could result in reduced recurrence. Preliminary evidence suggests a potential role for the VGKC subtypes Kv5.1, Kv7.2, and the Kv4 subfamily in GBM and DMG, due to observed upregulation of these genes in both patient-derived cell lines and tumour samples. These particular VGKC subtypes are highly novel with regards to these cancers, while their significant upregulation suggests they may be associated with tumour progression. Thus, we aim to further explore the relationship between ion channel function and tumourigenesis in GBM and DMG, with a specific focus on VGKC subtypes and their potential therapeutic value.